Kinerja RSUD Wangaya Kota Denpasar Berbasis Balanced Scorecard - Wahyuni, Tri Wahyuni; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.02.TAHUN 2018, 2018)
The research discusses the performance measurement of General Hospital of Wangaya Denpasar City as public sector organization with status of Regional Public Service Agency by using method of Balanced Scorecard (BSC). The purpose of the research was to investigate and analyze the performance of General Hospital of Wangaya City Denpasar comprehensively by Balanced Scorecard method for three years from 2014 to 2016, covering four perspectives: customer perspective, financial perspective, internal business process perspective, and perspective of learning and growth. The results of the study showed that the overall performance measurement of the hospital obtained a score of 73%, with qualification of good rating with success rate classified as successful..